“Painted buffalo horns”: imagery from the South African War - Ward, Val; Wintjes, Justine (Southern African Humanities, 2018)
Several cattle horns engraved with scenes inspired by the Anglo-Zulu War of 1879 are attributed to an unnamed Zulu artist from the Newcastle district of the Colony of Natal, South Africa. The pair of engraved horns illustrated and described here are attributed to a “native” artist in the Bedford district of the eastern Cape Colony, South Africa. They are decorated with scenes from the South African War (1899–1902). The Bedford horns depart from the ordered design of the nineteenth-century exemplars with their flowing pattern, and their use of colour. Whereas the work of the Artist of Newcastle involved repetitive depictions framed within small panels and often related to the formal flaunting of power, the Artist of Bedford described chaotic and organically linked scenes of interpersonal combat in a mode more akin to landscape. Working in different contexts, the two artists produced different expressions of a common artistic genre for an early craft market within a spreading cash-economy.